Ability to enjoy the community support and perception of violence among viewers in pairs (bullying) - Quintana Peña, Alberto (2010)
In a sample of adolescent viewers of violence between couples studied the relations between the ability to enjoy the individual and their perception of community support in school, in order to verify whether these variables are positively correlated with each other, and that there significant differences between the types of viewers of violence between couples in relation to them. This was used as operational indicators of these processes: Scale Padrós Gaudiability, the Scale of Perceived Community Support tailored to the school environment, and Type Scale Peer Violence Viewer validated in a previous study. We found significant positive correlations between the capacity of enjoyment and perceptions of community support in school among adolescents, as well as the various components of the latter. Equally significant differences in the ability to enjoy the individual and the perception of community support in school, between the viewer and the types of prosocial amoral and indifferent spectator blame, but there were no significant differences between these processes past.